Yeast diversity in blue mould ripened cheeses - De Jager, Paul Human (University of the Free State, 2003)
Blue veined cheese is considered a speciality cheese and is not as popular as other cheese varieties, such as Cheddar or Gouda. Their popularity is however increasing worldwide making it important to study their microbiological, biochemical and technological properties. The aims of this study was consequently to elicit the establishment, growth and survival of yeasts during the ripening of blue veined cheese varieties and to study the interactions between yeasts and the different microbial groups which occur during the ripening process. The enumeration of yeasts in foodstuffs with a high mould concentration proves to be difficult since yeasts are easily overgrown by the rapidly spreading moulds. This makes the enumeration, isolation and identification of yeasts difficult, hence also eliciting the ecological role of yeasts during the ripening of blue veined cheese varieties. Ten different selective media, containing anti-myctotic properties, were evaluated for their ability to suppress the growth and spreading of moulds and enhance the enumeration and recovery of yeasts from blue veined cheese. Quantitatively no statistical difference between the ten different media was detected. Qualitatively, however OGGY, MEA + SP and molybdate containing media could not be recommended. All other media performed satisfactory while MEA + Ox and MEA + BP gave superior results based on ease of isolation and enumeration. The usage of MEA + NaCl gave comparable results, but inhibited the growth of some of the yeast species most frequently found in ripening blue veined cheese varieties, when evaluated individually. Yeasts are one of the main microbial groups that occur during the ripening of blue veined cheese varieties, originating as post-pasteurisation contaminants. In chapter 3 the development of yeasts derived mainly from the dairy environment and their establishment during the ripening process was examined. They continued to dominate until the end of the ripening period, in meaningful numbers. Yeast species isolated and identified corresponds with those obtained by other researchers on similar cheese varieties. A 10 to 100 fold difference in yeast numbers were observed during the ripening period between the exterior and interior. Debaryomyces hansenii once again predominated in the present study. This is due to its ability to produce extracellular proteases and lipases and the species high tolerance towards low temperatures and high salt concentrations. Although yeasts are one of the major microbial groups present in blue veined cheese other microorganisms like Penicillium roqueforti and several different bacterial genera are also frequently encountered. All of these organisms collectively contribute to the final flavour and aroma of the product based on interactive proliferation. Consequently it was necessary to study the interactions between these organisms to improve our understanding of the ripening process and the contribution each organism makes to the process. Interaction studies in Chapter 4 revealed that various interactions occurred between yeasts and Penicillium roqueforti, as well as yeasts and bacteria essential to the final outcome of the product. The majority of yeast-bacterial interactions were neutral, although some interactions were antagonistic and stimulative. Debaryomyces hansenii was the most stimulatory yeast species towards bacterial isolates while Torulospora delbrueckii was the most antagonistic. All three microbial groups studied dominated throughout the ripening period and were present in meaningful numbers at the end of the ripening period.

Blou kaas variante word as ‘n spesialiteits kaas beskou en is derhalwe nie so gewild soos ander variante, byvoorbeeld Gouda en Cheddar. Die gewildheid van die tipe kase neem egter wêreldwyd toe. Om dié rede is dit dus belangrik om die mikrobiologiese, biochemiese en tegnologiese aspekte van die kase te bestudeer. Die doel van die studie was om die ontstaan, groei en oorlewing van giste tydens die rypwordingsproses van blou kaas variante te bestudeer, asook die interaksies wat plaasvind tussen die verkillende mikrobiese groepe tydens rypwording. Die optelling van giste in voedsel met ‘n hoë konsentrasie skimmels is moeilik aangesien die skimmels die giste oorgroei. Dit maak die optelling, isolasie en identifikasie van giste moeilik en gevolglik ook die bestudering van die ekologiese rol van giste tydens die rypwording van blou kaas variante. Tien verskillende selektiewe media wat anti-mikotiese middels bevat is getoets vir hul vermoë om die groei en verspreiding van skimmels te inhibeer. Hulle is ook getoets vir hul vermoë om te help met die optelling en isolasie van giste vanaf die blou kaas variante. Kwantitatief was daar geen statistiese verskil tussen die tien selektiewe media. Volgens kwalitatiewe data kon OGGY, MEA + SP en molibdaat bevatende media nie aanbeveel word nie. Al die ander media het bevredigend vertoon. MEA + Ox en MEA + BP het die beste resultate gelewer gebasseer op die feit dat isolasie en optelling vergemaklik was. MEA + NaCl het eenderse resultate getoon maar het die groei van sekere individuele gis spesies wat mees algemeen in blou kaas variante voorkom geinhibeer. Giste vorm een van die hoof mikrobiese groepe wat voorkom tydens die rypwording van blou kaas variante en ontstaan as post-pasteurisasie kontaminante. In hoofstuk 3 is die ontstaan en ontwikkeling van giste uit die omgewing bestudeer. Gis spesies wat geisoleer en geidentifiseer is stem ooreen met die wat verkry is deur ander navorsers op soortgelyke blou kaas variante. ‘n Tien- to honderd-maal verskil in gis tellings tussen die buite- en binnekant van die kaas is gevind gedurende die rypwordingsproses. Debaryomyces hansenii was oorheersend gedurende die studie. Die redes hiervoor is die vermoë van die spesie om ekstra-sellulêre proteases en lipases te produseer asook ‘n toleransie ten opsigte van lae temperature en hoë sout konsentrasies. Alhoewel giste een van die hoof groepe is wat voorkom tydens die rypwording van blou kaas variante is daar ook ander groepe, soos Penicillium roqueforti en verskeie bakteriële groepe. Al hierdie organismes dra gesamentlik by tot die finale geur en aroma van die kaas gebasseer op die interaksies wat hul ondergaan. Daarom is dit belangrik om hierdie verskillende interaksies te bestudeer om sodoende meer te wete te kom aangaande die rypwordings proses, asook die rol en bydrae van elke organisme. Interaksie studies wat uitgevoer is in hoofstuk 4 het aangedui dat verskeie interaksies bestaan tussen giste en Penicillium roqueforti, asook tussen giste en bakterieë, wat essensieël is vir die finale produk. Die meerderheid gis-bakterië interaksies was neutraal alhoewel sommige ook antagonisties en stimuleerend was. Debaryomyces hansenii was die mees stimulerende gis spesie ten opsigte van bakterieë en Torulaspora delbrueckii was die mees antagonisties. Al drie mikrobiese groepe wat bestudeer is het gedurende die rypwordings proses voorgekom en was teenwoordig in betekenisvolle getalle aan die einde van die rypwordingsproses.
Dissertation (M.Sc. (Microbiology, Biochemistry and Food Sciences))--University of the Free State, 2003
Keywords: Blue cheese; Yeasts; Lactic acid bacteria; Moulds; Identification; Selective media; Interactions; Antagonistic; Stimulate; Secondary bacteria; Cheese -- Microbiology; Cheesemaking